Answer:
The first mechanic worked for 20 hours and the second mechanic worked for 5 hours
Step-by-step explanation:
Let f be the number of working hours of first mechanic
Let s be the number of working hours of second mechanic
Given that they both worked for a combined total of 25 hours
⇒f + s = 25 → equation 1
First mechanic charged $95 per hour and second mechanic charged $90 per hour and they both together charged $2350
⇒95f + 90s = 2350 → equation 2
Using equation 1 in equation 2:
95f + 90(25-f) = 2350
⇒95f + 2250 - 90f = 2350
⇒5f = 100
or f = 20 hours
⇒s = 25 - f ⇒ s = 5 hours
The first mechanic worked for 20 hours and the second mechanic worked for 5 hours
Georgia's baby brother weighed less than 11 pounds when he was born. Which of the following could be the number of ounces Georgia's baby brother weighed? Select two that apply.
A
156 ounces
B
170 ounces
C
186 ounces
D
190 ounces
Answer:
Step-by-step explanation:
B :because 11 pound in Ounces is 176
What is 7225 / 8 with the remainder as a whole number
Answer:
903 1/8
Step-by-step explanation:
Just divide 7225 by 8. :) I put it in fraction form but decimal form is just 903.125. I hope this helps you out. :)
Answer:
its 903 with 1 left over
help, succession formula
Answer:
[tex]a_n=-3*\left ( -\frac{2}{3} \right )^n \ n>=0[/tex]
Step-by-step explanation:
Succession can be understood as a sorted collection of values that respond to a general term or rule. We need to find if these numbers are in arithmetic progression or geometric progression.
In an arithmetic progression, every number is obtained as the previous number plus or minus a constant value called common difference. In a geometric progression, we get the next numbers as the previous one multiplied or divided by a constant value, called the common ratio.
If we try to find a possible common difference between first and second terms we get:
[tex]2-(-3)=5[/tex]
If it was an arithmetic progression, third term should be
[tex]2+5=7[/tex]
Which is obviously not true. Now let's try to find a possible common ratio by dividing second by first term
[tex]r=\frac{2}{-3}=-\frac{2}{3}[/tex]
Testing our value to find the third term we get
[tex]a_3=2*(-\frac{2}{3})=-\frac{4}{3}[/tex]
Since we have more terms to test:
[tex]a_3=(-\frac{4}{3})*(-\frac{2}{3})=\frac{8}{9}[/tex]
The given value is just as predicted
The fourth term can be accurately predicted also:
[tex]a_4=(\frac{8}{9})*(-\frac{2}{3})=\frac{16}{27}[/tex]
Now we are sure it's a geometric progression, it can easily be stated the general term of the progression is
[tex]a_n=a_1*r^n \ n>=0[/tex]
[tex]a_n=-3*\left ( -\frac{2}{3} \right )^n \ n>=0[/tex]
2.c is anyone good with exponential and logarithmic?
Answer:
After 48 months the value will increase by 10 percent of the initial value.Step-by-step explanation:
Let's first find the rate of increase for each period which is 3 months here.
According to the table at month [tex]x=0[/tex] value is [tex]2000[/tex]dollars and at month [tex]x=3[/tex] value is [tex]2012[/tex]dollars.
∴[tex]2012=2000(1+\frac{r}{100} )^1[/tex]
⇒[tex]1+\frac{r}{100} =\frac{2012}{2000}=1.006[/tex]
⇒[tex]r=0.006*100[/tex]
⇒[tex]r=0.6[/tex]%
Now the question is to find how long it will take for the investment value to increase 10 percent.
[tex]y=2000(1+0.006)^\frac{x}{3}[/tex]
[tex]2000(1+0.1)=2000(1.006)^\frac{x}{3}[/tex]
⇒[tex](1.006)^\frac{x}{3} =1.1[/tex]
⇒[tex]\frac{x}{3}=\frac{log(1.1)}{log(1.006)}[/tex]
⇒[tex]x=3(\frac{log(1.1)}{log(1.006)} )[/tex]
⇒[tex]x=47.7979126....[/tex]
∴at [tex]x=48[/tex] the value will slightly cross 10 percent increase.
The ____ value of a digit is based on its location.
Answer:
place
Step-by-step explanation:
Answer:
The answer is " Place value"
Step-by-step explanation:
The place value determines the value of the digit in a number, based on its position.
A standard form number is divided into groups of three digits using commad. Each of these groups is called a period.
SOS PLEASE HELP so I don't fail math
Answer:
2 years ago :/
Step-by-step explanation:
PLZZ HELP!!! NEED ANSWER QUICKLY!!!!
Describe and correct the following error for evaluating the function g(x)=-5x+3 when x=-3.
g(-3)=(-5)(-3)+3=-3g+g=-6
plz show step by step how you solved it
Answer:
The value of g(x) at x = -3 is 18.
Step-by-step explanation:
Here, the given function is:
g(x) = - 5 x + 3
Now, for the value of x = -3 ,
g (-3) : Substitute the value of x = -3 in g(x) , we get
g (-3) = -5 (-3) + 3
= 15 + 3 = 18
or, g ( -3) = 18
Hence, the value of g(x) at x = -3 is 18.
The horizontal line segment at the top of the polygon on the grid below is how many units long?
Answer:
6 units long.
Step-by-step explanation:
Given:
A polygon drawn on a graph.
In order to determine the distance of the horizontal line at the top, we find the coordinates of the end points and then use distance formula to find the exact distance.
Let us label the polygon as ABCD as shown below. AB is the length of the horizontal line.
Coordinates of A are [tex](x_1,y_1)=(-3, 4)[/tex] as seen in the graph.
Coordinates of B are [tex](x_2,y_2)=( 3, 4)[/tex] as seen in the graph.
Now, distance formula for two points [tex](x_1,y_1)\ and\ (x_2,y_2)[/tex] is:
[tex]d=\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}\\d_{AB}=\sqrt{(3-(-3))^2+(4-4)^2}\\d_{AB}=\sqrt{(3+3)^2+0}\\d_{AB}=\sqrt{36}=6\ units[/tex]
Therefore, the horizontal line at the top is 6 units long.
Answer:
6 units long
Step-by-step explanation:
brainly patrol what is wrong with that
Carlotta has 12 2/3 yd of ribbon to be divided among 19 girls in the cheerleading squad.how much ribbon will each girl get if it is divided equally among the 19 girls
Answer:
Each girl gets 2/3 yd of ribbon.
Step-by-step explanation:
12 2/3=38/3
(38/3)/19
(38/3)(1/19)
(2/3)(1/1)=2/3
Make b the subject of the formula
[tex]a = \sqrt{b + 6} [/tex]
Answer:
a^2 -6
Step-by-step explanation:
use ur basic knowing of equations
Which expression is equivalent to
First choice: m^32n^16
Hope this helps!
Answer:
The correct answer would be m^32n^16.
Step-by-step explanation:
This is because when you have a power inside parenthesis multiplied by a power outside the parenthesis, you are simply going to multiply the numbers like so:
8 • 4 = 32
4 • 4 = 16
m^32n^16
Hope this helps,
♥A.W.E.S.W.A.N.♥
In recent year 34% of all college students were enrolled part time if 6.1 million college students were enrolled part time that year what was the total number of college students
The total number of college students was 17.94 million.
Step-by-step explanation:
Percentage of part time students = 34%
Number of part time students = 6.1 million
Let,
x be the total number of students
According to statement,
34% of x = 6.1 million
[tex]\frac{34}{100}x=6.1\ million\\0.34x=6.1[/tex]
Dividing both sides by 0.34
[tex]\frac{0.34x}{0.34}=\frac{6.1}{0.34}\\x=17.94\ million[/tex]
The total number of college students was 17.94 million.
Keywords: percentage, division
Learn more about division at:
brainly.com/question/11638377brainly.com/question/11921476#LearnwithBrainly
What is the y-intercept of y = 5?
Answer:
Y- intercept is 5!
How many solutions does this system of equations have?
exactly one
exactly two
infinitely many
none
Answer:
exactly one
Step-by-step explanation:
1. subtract 2x from the equation 2x + y = 1
2. now you should have y= -2x + 1
3. then on the second equation subtract 4x from 4x + 2y = 2
4. now you should have 2y = -4x + 2
5. divide everything by 2
6. now you should have y = -2x + 1
7. since you got an exact answer on both of them then it is exactly one
Determine whether the following statements are true or false. If false, explain why.
1) Point (3,2) to (3,-2) is a reflection over the y-axis.
2) A(1,3) to A'(-1,3) is a reflection over the y-axis
Answer:
see the explanation
Step-by-step explanation:
we know that
The rule of the reflection of a point across the y-axis is equal to
(x,y) -----> (-x,y)
The rule of the reflection of a point across the x-axis is equal to
(x,y) -----> (x,-y)
so
Verify each statement
1) Point (3,2) to (3,-2) is a reflection over the y-axis.
The statement is false
Because, is a reflection over the x-axis
A reflection over the y-axis will be
(3,2) -----> (-3,2)
2) A(1,3) to A'(-1,3) is a reflection over the y-axis
The statement is true
• What ratio is equivalent to 6 to 2? Complete the statement.
)) The ratio 6 to 2 is equivalent to the ratio
to ?
3 to 1
The ratio 6 to 2 is equivalent to the ratio 3 to 1, obtained by dividing both the numerator and denominator of the ratio by their greatest common divisor, which is 2.
Explanation:To find a ratio equivalent to 6 to 2, you simplify the ratio by dividing both numbers by their greatest common factor. In this case, the greatest common factor is 2, so 6 ÷ 2 = 3 and 2 ÷ 2 = 1. Therefore, the equivalent ratio is 3 to 1.
The ratio 6 to 2 can be simplified by dividing both numbers by their greatest common divisor, which is 2. Therefore, 6 divided by 2 is 3, and 2 divided by 2 is 1. This simplification shows that the ratio 6 to 2 is equivalent to 3 to 1. Ratios compare two quantities and can be expressed in several forms such as fractions, with a colon, or using the word "to". An equivalent ratio maintains the same proportional relationship between its components, just like how 6:2 has the same proportional relationship as 3:1.
Cos(theta)= -.9041, 180degress< theta <270degress
Answer:
[tex]\theta=205.298^o[/tex]
Step-by-step explanation:
We know
[tex]cos\theta=-.9041[/tex]
in the third quadrant [tex]180^o<\theta<270^o[/tex]
We use a scientific calculator to find the inverse cosine of -0.9041 to find
[tex]\theta=154.702^o[/tex]
Since this angle is not in the required quadrant we must find the other angle who has the same cosine. The required angle is equidistant from the found value from the 180 degrees angle, so our solution is
[tex]\theta=180^o+(180^o-154.702)=205.298^o[/tex]
A rectangle has an area of 24 sq. inches and a perimeter of 50 in. what are the dimensions of the rectangle
Final answer:
To find the dimensions of a rectangle with an area of 24 sq. inches and a perimeter of 50 inches, we set up a system of linear equations and solve for the length and width. The dimensions are found to be either 24 inches by 1 inch or 1 inch by 24 inches.
Explanation:
The question given by a student involves finding the dimensions of a rectangle given its area and perimeter. Given the area (24 sq. inches) and the perimeter (50 in.), we can set up two equations to solve for the length and width:
Area = length imes width = 24 sq. inches
Perimeter = 2 imes (length + width) = 50 inches
We can divide the perimeter by 2 to get the sum of the length and width:
25 = length + width
Since we have two equations, this forms a system of linear equations which we can solve simultaneously. First, assume the length is the larger dimension and let us represent it by 'L' and the width by 'W'. We have:
L imes W = 24
L + W = 25
To solve for L and W, we can use substitution or elimination methods. Let's assume we solve for W in terms of L using the first equation, W = 24/L, and then we substitute it into the second equation:
L + 24/L = 25
Multiplying both sides by L to clear the fraction, we get:
L² + 24 = 25L
Then we rearrange the terms to set the equation to zero:
L² - 25L + 24 = 0
Now we can factor this quadratic equation to find the values of L:
(L - 1)(L - 24) = 0
So, L can be either 1 inch or 24 inches. If L is 24 inches, then W will be 1 inch (since 24 imes 1 = 24), and if L is 1 inch, then W will be 24 inches. Either way, the dimensions that satisfy both the area and perimeter equations are 24 inches by 1 inch.
The dimensions of the rectangle are [tex]\( {24 \text{ inches} \text{ by } 1 \text{ inch}} \)[/tex].
To find the dimensions of the rectangle, let's denote the length by l and the width by w.
Given:
1. The area of the rectangle is 24 square inches:
[tex]\[ l \cdot w = 24 \][/tex]
2. The perimeter of the rectangle is 50 inches, which gives us the equation:
[tex]\[ 2l + 2w = 50 \][/tex]
Let's solve these equations step by step.
From the perimeter equation:
[tex]\[ 2l + 2w = 50 \][/tex]
Divide the entire equation by 2 to simplify:
[tex]\[ l + w = 25 \][/tex]
Now we have two equations:
[tex]\[ l + w = 25 \]\[ l \cdot w = 24 \][/tex]
Let's solve for l and w using substitution or elimination.
From ( l + w = 25 ), we can express l as:
[tex]\[ l = 25 - w \][/tex]
Substitute [tex]\( l = 25 - w \)[/tex] into [tex]\( l \cdot w = 24 \)[/tex]:
[tex]\[ (25 - w) \cdot w = 24 \][/tex]
Expand and rearrange the equation:
[tex]\[ 25w - w^2 = 24 \]\[ w^2 - 25w + 24 = 0 \][/tex]
Now, solve this quadratic equation using the quadratic formula [tex]\( w = \frac{{-b \pm \sqrt{{b^2 - 4ac}}}}{{2a}} \)[/tex], where ( a = 1 ), ( b = -25 ), and ( c = 24 ):
[tex]\[ w = \frac{{-(-25) \pm \sqrt{{(-25)^2 - 4 \cdot 1 \cdot 24}}}}{{2 \cdot 1}} \]\[ w = \frac{{25 \pm \sqrt{{625 - 96}}}}{2} \]\[ w = \frac{{25 \pm \sqrt{{529}}}}{2} \]\[ w = \frac{{25 \pm 23}}{2} \][/tex]
So, we get two possible values for w:
[tex]\[ w = \frac{{25 + 23}}{2} = 24 \]\[ w = \frac{{25 - 23}}{2} = 1 \][/tex]
Now, find l for each value of w:
1. If ( w = 24 ):
[tex]\[ l = 25 - 24 = 1 \][/tex]
2. If ( w = 1 ):
[tex]\[ l = 25 - 1 = 24 \][/tex]
find the slope between the points (-4,5) and (-8,-5)
Answer:
[tex] \frac{5}{2} \\ [/tex]
Step-by-step explanation:
[tex] \frac{ - 5 - 5}{ - 8 - - 4} [/tex]
Y - Y divided by X - X, the Y is 5 and the X is 2 (Rise over Run)
Answer:
[tex]\displaystyle 2\frac{1}{2} = m[/tex]
Step-by-step explanation:
[tex]\displaystyle \frac{-y_1 + y_2}{-x_1 + x_2} = m \\ \\ \frac{-5 - 5}{4 - 8} = \frac{-10}{-4} = 2\frac{1}{2}[/tex]
I am joyous to assist you anytime.
A class of 32 consists of students who either have red or yellow shirts if there are 12 more people with red shirts in there are people with yellow shirt many students have red shirt
Answer:
22 people with red shirts and 10 people with yellow shirts
Help with number 15 with the graph
Answer:
I believe it is 7
Step-by-step explanation:
An employee of a car wash earns $12 for each car she washes. She always saves $50 of her weekly earnings. This week, she wants to have at least $100 in spending money. Write an inequality to find the fewest number of cars she must wash.
the inequality representing the fewest number of cars she must wash is [tex]\( x \geq 13 \).[/tex]
To find the fewest number of cars the employee must wash, we need to determine the minimum number of cars that will allow her to have at least $100 in spending money after saving $50.
Let's denote the number of cars she must wash as( x \).
Given:
- Earnings per car washed: $12
- Amount saved: $50
- Desired spending money: at least $100
Step 1: Calculate her earnings from washing cars:
The total earnings from washing cars will be ( 12x ) dollars.
Step 2: Calculate her spending money after saving:
She saves $50 of her weekly earnings, so her spending money will be her total earnings minus $50, which is \( 12x - 50 \) dollars.
Step 3: Write the inequality:
Since she wants to have at least $100 in spending money, we can write the inequality:
[tex]\[ 12x - 50 \geq 100 \][/tex]
This inequality states that her spending money after saving must be greater than or equal to $100.
Now, to solve for [tex]\( x \), we'll isolate \( x \)[/tex] on one side of the inequality.
Step 4: Solve the inequality:
[tex]\[ 12x - 50 \geq 100 \][/tex]
Add 50 to both sides:
[tex]\[ 12x \geq 150 \][/tex]
Now, divide both sides by 12:
[tex]\[ x \geq \frac{150}{12} \][/tex]
[tex]\[ x \geq 12.5 \][/tex]
Step 5: Interpret the result:
Since the number of cars washed must be a whole number (you can't wash half a car), the fewest number of cars she must wash to have at least $100 in spending money is 13.
So, the inequality representing the fewest number of cars she must wash is [tex]\( x \geq 13 \).[/tex]
Assume that µ = 500 and s = 100. Your study shows a sample of size 22 with a mean of 530 and standard deviation of 113. a. What is the most powerful test to use to test the hypothesis that the mean of the sample was drawn from the above Null Hypothesis Population? b. What is the value of the test statistic? c. What do you conclude using a = 0.052 tail?
Answer: using t - test value is 1.37<2.08( At 0.05 level of significance)
The mean of the sample was drawn from the population.
Step-by-step explanation:
Here sample size n=22
Given sample mean =530
Given population mean =500
[tex]t=\frac{sample mean-µ}{\frac{S}{\sqrt{n-1} } }[/tex]
given sample standard deviation s=100
a) null hypothesis:- The mean of the sample was drawn from the population µ =500
Alternative hypothesis:-
The most powerful test you can use is t - distribution.
The test statistic is
[tex]t=\frac{sample mean- µ}{\frac{S}{\sqrt{n-1} } }
here S is the standard deviation of the sample
b) The value of the test statistic
[tex]t=\frac{sample mean- µ}{\frac{S}{\sqrt{n-1} } }
substitute given values sample size n=22
sample mean =530
sample standard deviation s =100
mean of the population µ =500
the calculated value of t =[tex]\frac{530-500}{\frac{100}{\sqrt{22} } }[/tex]
the calculated value=1.3748
c) The degrees of freedom =n-1 = 22-1 = 21
The table value of t are 0.05 level of significance with 21 degrees of freedom is 2.08
The calculated value 1.37<2.08
∴ we accept null hypothesis at 0.05 level of significance
conclusion:-
The mean of the sample was drawn from the population.
A t-test is the most powerful test for this hypothesis. The test statistic value is calculated using t = (X - µ) / (s / √n). Based on a significance level of 0.05, we can conclude by comparing the calculated t-value with the critical t-value from t-distribution table.
Explanation:The subjects of this question are hypothesis testing and statistics.
To answer your question: a) The most powerful test to use to test your hypothesis is the t-test for single mean. This is because you have one sample mean, one hypothesized population mean, and the population standard deviation is not known.
b) The value of the test statistic can be calculated using the formula: t = (X - µ) / (s / √n), where X is the sample mean, µ is the population mean, s is the sample standard deviation, and n is the sample size. Plugging in your values, the formula becomes t = (530 - 500) / (113/ √22).
c) With a = 0.05, we conclude by comparing the calculated t-value with t-distribution table (df = 22-1 = 21). If the calculated t-value exceeds the critical t-value from the t-distribution table, we reject the null hypothesis.
Learn more about Hypothesis Testing here:https://brainly.com/question/34171008
#SPJ11
This pair of figures is similar. Find the missing side.
Answer:
x=2
Step-by-step explanation:
so if the bigger one is 16 and the other one is 4 that means you need to multiply 4 by 4 to get 16 so to find x you need to divide the 8 by 4 to find your answer
Answer:
x = 2
Step-by-step explanation:
Since the triangles are similar then the ratios of corresponding sides are equal, that is
[tex]\frac{x}{8}[/tex] = [tex]\frac{4}{16}[/tex] ( cross- multiply )
16x = 32 ( divide both sides by 16 )
x = 2
Following a translation, the measures of the angles in a pre-image are congruent to the measures of the corresponding angles in its image.
True
False
Triangle DEF (not shown) is similar to ABC shown, with angle B congruent to angle E and angle C congruent to angle F. The length of side DE is 6 cm. If the area of ABC is 5 square centimeters, what is the area of DEF ?
Answer:
Area of ΔDEF is [tex]45\ cm^2[/tex].
Step-by-step explanation:
Given;
ΔABC and ΔDEF is similar and ∠B ≅ ∠E.
Length of AB = [tex]2\ cm[/tex] and
Length of DE = [tex]6\ cm[/tex]
Area of ΔABC = [tex]5\ cm^2[/tex]
Solution,
Since, ΔABC and ΔDEF is similar and ∠B ≅ ∠E.
Therefore,
[tex]\frac{Area\ of\ triangle\ 1}{Area\ of\ triangle\ 2} =\frac{AB^2}{DE^2}[/tex]
Where triangle 1 and triangle 2 is ΔABC and ΔDEF respectively.
If two triangles are similar, then the ratio of the area of both triangles is proportional to the square of the ratio of their corresponding sides.
[tex]\frac{5}{Area\ of\ triangle\ 2} =\frac{2^2}{6^2}\\ \frac{5}{Area\ of\ triangle\ 2}=\frac{4}{36}\\ Area\ of\ triangle\ 2=\frac{5\times36}{4} =5\times9=45\ cm^2[/tex]
Thus the area of ΔDEF is [tex]45\ cm^2[/tex].
What are some math equations that end up making the answer being 209
Answer:
Step-by-step explanation:
(0^209 + 1(209)/(209))^0 + 208
A bag contains purple marbles and white marbles, 34 in total. The number of purple marbles is 1 less than 4 times the number of white marbles. How many purple marbles are there?
There are 27 purple marbles
Step-by-step explanation:
Let p be the purple marbles
and
w be the white marbles
Then according to given statements
[tex]p+w = 34\ \ \ Eqn\ 1\\p = 4w-1\ \ \ Eqn 2[/tex]
Putting p = 4w-1 in equation 1
[tex]4w-1 +w = 34[/tex]
Adding one on both sides
[tex]5w-1+1 = 34+1\\5w = 35[/tex]
Dividing both sides by 5
[tex]\frac{5w}{5} = \frac{35}{5}\\w = 7[/tex]
Putting w = 7 in equation 2
[tex]p = 4(7)-1\\p = 28-1\\p = 27[/tex]
Hence,
There are 27 purple marbles
Keywords: Linear equation
Learn more about linear equations at:
brainly.com/question/2116906brainly.com/question/2131336#LearnwithBrainly
I need help with this math problem.
===============================================
Explanation:
The x intercept is (-2,0) which is where the graph crosses the x axis.
The y intercept is (0,-6) which is where the graph crosses the y axis.
-----
Find the slope of the line through those two points
m = (y2-y1)/(x2-x1)
m = (-6-0)/(0-(-2))
m = (-6-0)/(0+2)
m = -6/2
m = -3
-----
The y intercept (0,-6) leads to b = -6
Both m = -3 and b = -6 plug into y = mx+b to get
y = mx+b
y = -3x+(-6)
y = -3x-6
-----
Now add 3x to both sides
y = -3x-6
y+3x = -3x-6+3x
3x+y = -6
-----
Lastly, multiply both sides by -2 so that the "-6" on the right hand side turns into "12" (each answer choice has 12 on the right hand side)
3x+y = -6
-2(3x+y) = -2(-6)
-2(3x)-2(y) = 12
-6x-2y = 12
which is what choice B shows.
Evaluate the expression –0.4(3x – 2) + StartFraction 2 x plus 4 Over 3 EndFraction for x = 4
Answer:
[tex]-0.4(3x-2)+\frac{2x+4}{3}=0\ \textrm{for}\ x=4[/tex]
Step-by-step explanation:
Given:
The expression to evaluate is given as:
[tex]-0.4(3x-2)+\frac{2x+4}{3}[/tex]
The value of 'x' is 4.
Plug in 4 for 'x' in the above expression and simplify. This gives,
[tex]=-0.4(3(4)-2)+\frac{2(4)+4}{3}\\=-0.4(12-2)+\frac{8+4}{3}\\=-0.4(10)+\frac{12}{3}\\=-4+4\\=0[/tex]
Therefore, the value of the given expression for 'x' equal to 4 is 0.
The required value of the given expression is 0 when substituting the value of x = 4 into the expression.
The expression is given as follows:
-0.4(3x - 2) + (2x + 4) / 3
Let's evaluate the given expression for x = 4:
Expression = -0.4(3x - 2) + (2x + 4) / 3
Substitute x = 4 into the given expression:
Expression = -0.4(3 × 4 - 2) + (2 × 4 + 4) / 3
Expression = -0.4(12 - 2) + (8 + 4) / 3
Expression = -0.4(10) + 12 / 3
Expression = -4 + 12 / 3
Expression = -4 + 4
Expression = 0
Therefore, when x = 4, the value of the expression is 0.
Learn more about Expressions here :
brainly.com/question/21751419
#SPJ3